2018
DOI: 10.3390/molecules24010063
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Glutaraldehyde Activation Study on HCl-Doped PVA–PANI Copolymers with Different Aniline Concentrations

Abstract: In this work, we report the synthesis and purification of polyvinyl alcohol-polyaniline (PVA–PANI) copolymers at different aniline concentrations, and their molecular (1H-NMR and FTIR), thermal (TGA/DTG/DSC), optical (UV–Vis-NIR), and microstructural (XRD and SEM) properties before and after activation with glutaraldehyde (GA) in order to obtain an active membrane. The PVA–PANI copolymers were synthesized by chemical oxidation of aniline using ammonium persulfate (APS) in an acidified (HCl) polyvinyl alcohol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Conductive polymers have been studied, owing to their distinctive properties, since they were discovered in 1977 [10]. Polypyrrole (PPy) has gained much attention as one of the most common conductive polymers due to its conductivity, pseudo-capacitive performance, and ease of synthesis for application in sensors, catalysis, energy storage and conversion, corrosion protection, and electromagnetic interference shielding [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers have been studied, owing to their distinctive properties, since they were discovered in 1977 [10]. Polypyrrole (PPy) has gained much attention as one of the most common conductive polymers due to its conductivity, pseudo-capacitive performance, and ease of synthesis for application in sensors, catalysis, energy storage and conversion, corrosion protection, and electromagnetic interference shielding [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The methylene proton signal appeared at 3.34 ppm (a) and the aromatic protons attached to the benzenoid and quinoid rings of PABA showed the multiplet signals 6.55–7.31 ppm (b–i). It could be concluded that the synthesis of PABA from the ABA monomer using APS as an oxidant was successful in this study [ 36 , 45 ].…”
Section: Resultsmentioning
confidence: 90%
“…In the region from 150 • C to 270 • C, there was a gradual weight loss of 7.10 wt%, corresponding to the loss of the adipic acid used as a dopant molecule [45]. The third step saw a weight loss of 9.03 wt%, possibly due to the degradation of functional groups and oligomers [46,47]. In the final step, the mass loss initiated at 360 • C was ascribed to the PNMA backbone degradation.…”
Section: Resultsmentioning
confidence: 99%